HUBUNGAN ADAPTASI KEHAMILAN PADA IBU HAMIL RISIKO TINGGI DENGAN PRENATAL ATTACHMENT DI PUSKESMAS DENDANG KABUPATEN TANJUNG JABUNG TIMUR - Mareta Tiodoria Situmorang; Herinawati Herinawati; Netti Herawati; Suryani Suryani; Iksaruddin Iksaruddin (NHM PRESS, 2022)
Complications during pregnancy can be categorized as a risk of pregnancy, as many as 90% of the causes of death occur due to unexpected obstetric complications during pregnancy, during delivery or after delivery and 15% of pregnancies are estimated to be high risk and can harm the mother and fetus. The purpose of this study was to determine the relationship between pregnancy adaptation in high-risk pregnant women and prenatal attachment. This study is a quantitative study using a cross-sectional research design with the aim of knowing the relationship between pregnancy adaptation in high-risk pregnant women and Prenatal Attachment carried out in the work area of ​​the Dendang Tanjung Jabung Timur Health Center in January-July 2022. The study population of all high-risk pregnant women was 57 mothers. pregnant women were taken by total sampling technique. This study used a prenatal attachment inventory (PAI) questionnaire to measure PA. After the data was collected, a univariate statistical test was performed using a frequency distribution for the respondent's characteristic variables and bivariate. Based on the results of the study, it was found that of the 57 respondents who had a good pregnancy adaptation, 41 (71.9%) respondents and 16 (28.1%) poor respondents, the Prenatal Attachment variable was known that as many as 51 (89.5%) respondents had high Prenatal Attachment and 6 (10.5%) respondents had low Prenatal Attachment. The results of statistical tests obtained p-value = 0.007, it can be concluded that there is a significant relationship between pregnancy adaptation in high-risk pregnant women and Prenatal Attachment. Suggestions from the study can be input for health workers, especially midwives to improve the provision of midwifery care to pregnant women, especially in the work area of ​​the Puskesmas and become the basis for the implementation of a program of guidance, guidance, and counseling activities in an effort to increase knowledge of pregnant women about the importance of prenatal care.